Manfaat Pembiasaan Istima’ dalam Pembelajaran Bahasa Arab Bagi Mahasiswa Pendidikan Bahasa Arab Universitas Pendidikan Indonesia - Salwa Azizah Rahman; Khoirunnisa Maharani; Arif Rahman Hakim; Muhammad Rifky Fauzan; Ahmad Fu’adi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
One of the basic skill methods to begin learning or mastering a foreign language, especially in Arabic is listening skills (istima'). So for teaching and learning foreign languages, especially Arabic, it is very important to have the ability to hear or listen (istima'). This istima' proficiency can help learners to easily understand a word that is heard well and clearly. The success of istima' learning is highly dependent on 3 stages, namely the planning stage (intention), the implementation stage, and finally the evaluation stage. Tools are very important to improve istima' skills such as media, both audio and audio-visual media. In this very modern era, habituation of istima' is very easy to do, because students do not need to visit Arab countries to be able to hear Arabic directly from local residents there, but students only need to open gadgets or other electronic devices such as laptops, computers, etc. to access audios or videos containing Arabic to help students in the process of habituation of istima'. If students have done istima' habituation regularly, then of course it will be easier for students to learn Arabic, because they have previously been accustomed to hearing it.